2006
DOI: 10.1007/s11745-006-5079-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between plasma antioxidant capacity and n−3 PUFA in red blood cells from women

Abstract: PUFA are susceptible to oxidation. However, the chain-reaction of lipid peroxidation can be interrupted by antioxidants. Whether an increased concentration of PUFA in the body leads to decreased antioxidant capacity and/or increased consumption of antioxidants is not known. To elucidate the relationship between plasma total antioxidant capacity (TAC), the concentration of antioxidant vitamins, and the proportion of PUFA in red blood cells (RBC), plasma TAC was measured by a Trolox equivalent antioxidant capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
1
17
1
2
Order By: Relevance
“…However, increased intake of EPA/ DHA has been reported to reduce in vivo lipid peroxidation and oxidative stress in humans [1,36]. A positive association between the n-3 PUFA content of red blood cells, which reflects the consumption of n-3 PUFAs, and plasma antioxidant capacity, has been also described [45]. In the present study, the consumption of n-3 PUFA-enriched juice did not produce any increase in lipid peroxidation, since MDA levels remained unchanged during the intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased intake of EPA/ DHA has been reported to reduce in vivo lipid peroxidation and oxidative stress in humans [1,36]. A positive association between the n-3 PUFA content of red blood cells, which reflects the consumption of n-3 PUFAs, and plasma antioxidant capacity, has been also described [45]. In the present study, the consumption of n-3 PUFA-enriched juice did not produce any increase in lipid peroxidation, since MDA levels remained unchanged during the intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Saito and Kubo (2003) reported that a-tocopherol in serum became lower with increasing degree of unsaturation of dietary polyunsaturated fatty acid. On the other hand, Thorlaksdottir et al (2006), using a human model, concluded that xÀ3 polyunsaturated fatty acids did not present adverse effect on plasma TBARS or plasma level of most antioxidant vitamins. No changes in plasma a-tocopherol concentration were observed among the groups and no lycopene was detected in plasma of animals supplemented with both doses.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with all other constituents of LDL, polyunsaturated fatty acids show the highest sensitivity to oxidation by molecular oxygen in function of the number of double bounds (Frankel, 2005;. Actually, whether a diet rich in EPA and DHA fatty acids, containing five and six double bonds respectively, leads to a decrease in antioxidant capacity and/or an increased consumption of antioxidants is not yet known (Kris-Etherton, Harris, & Appel, 2002;Thorlaksdottir et al, 2006;. Studies on the oxidation rate after ingestion of dietary EPA and DHA in both animal or human models have shown conflicting results (Luostarinen, Laasonen, & Calder, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os principais mecanismos estudados, está o efeito protetor contra arritmias (115)(116) , efeitos no perfil lipídico (117)(118) , principalmente redução dos níveis séricos de triglicerídeos (119)(120)(121) , efeito antioxidante (122)(123)(124)(125) e antiinflamatório (126)(127) . Em 2001, dois estudos demonstraram evidênci-as sobre o efeito favorável dos ácidos graxos ômega-3 na redução do risco de DMRI.…”
Section: G Omega-3unclassified